Sustainability status of technology application on rice farming in peatlands (case study at Kanamit Jaya village, Central Kalimantan) - Maulia Aries Susanti; Mamat H.S (Journal of Wetlands Environmental Management, 2017)
Peatlands become one of the potential resources that could be developed as an area of rice farming to improve national food security. Agricultural cultivation in peatlands, if not managed well, will contribute to environmental destruction and land degradation, which will ultimately affect land productivity. As a first step in preparing the development of rice farming, research on the application of technology has conducted. This research included water management, which consists of:Â  without water management or control (A0), macak-macak water management (A1) and intermittent water management (A2). Moreover, research on pesticide application was also conducted which consist of: without pesticide application or control (P0), Paraquat herbicide application at the time of tillage (P1), Fenobucarb insecticide applications every week (P2), Fenobucarb insecticide applications every two weeks (P3), Difenoconazole fungicide applications every week (P4), Difenoconazole fungicide applications every two week (P5).Â  This study aims to determine the level of sustainability of rice farming in peatlands, and the dominant factors that influence by considering economic, social and environmental through a Multi Dimensional Scaling (MDS) approach. The analysis shows a quite sustainable level, with score for each dimension is 53.13 for the economic dimension, 69.49 for the ecological dimension and 61.79 for the social dimension. The dominant factors to be considered for the sustainability of rice farming in peatlands are changes in the level of decomposition of organic matter, farming purpose and outreach intensity.